Three-Dimensional Fatigue Crack Growth Analysis Using Failure Mechanism Approach In Ansys - Ismail, Muhammad Dhirar As Suhaimi (Universiti Sains Malaysia, 2019)
Critical cracks exist mainly on surfaces of mechanical components in engineering. To predict fatigue crack propagation, fatigue crack growth life, and characterization of a surface crack through different simulation tool are widely being implemented. From fracture analysis it is known that the stress field in a 3D surface crack differs from the conventional plane strain tip field. The stress intensity factor (SIF) depends additionally on crack front curvature, crack edge to free surface, and structure configuration. Especially, SIF may vary non-proportionally with crack growth. Predictability and accuracy of the fracture mechanics to 3D surface crack are still interesting issue for many mechanical parts under different geometry and loading conditions. So, this thesis proposes Separating, Morphing, Adaptive, and Remeshing Technology (SMART) which is a new feature available in ANSYS version 19.0 and above to analyze fatigue crack growth under cyclic loading in 3D analysis. This research is to evaluate the fatigue crack growth (FCG) life, effect of geometric discontinuity variation and loading position different on the crack trajectory and fatigue life respectively. Finite element analysis (FEA) was performed on a test specimen taken from a published research to obtain the direction of crack propagation under fatigue loading. The analysis was executed using ANSYS 19.2 under mechanical workbench platform. The crack propagation on the specimen was simulated using Life-Cycle Prediction (LC) method under SMART feature. This thesis verifies the validity of this new feature for crack growth analysis and to portray the effect of geometric discontinuity variation and different loading application on the crack propagation angle and specimen fatigue life respectively. It was found that, geometric discontinuity and loading application variation give a major effect on the crack propagation angle and specimen’s fatigue life cycle. This also justify that the crack angle and fatigue life is influenced by loading position, geometric discontinuity and defect that present in the specimen.